2010
DOI: 10.3122/jabfm.2010.03.090124
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Cancer Screening among Urban Minority Women

Abstract: Purpose: To evaluate the association of intimate partner violence (IPV) with breast and cervical cancer screening rates.Methods: We conducted retrospective chart audits of 382 adult women at 4 urban family medicine practices. Inclusion criteria were not being pregnant, no cancer history, and having a partner. Victims were defined as those who screened positive on at least one of 2 brief IPV screening tools: the HITS (Hurt, Insult, Threat, Scream) tool or Women Abuse Screening Tool (short). Logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 31 publications
1
30
1
1
Order By: Relevance
“…One study has shown that women who were victims of sexual and/or physical violence were less likely to be up-to-date with their mammograms and Pap smear screenings. 44 It is likely that the Behavioral Model of Vulnerable Populations applies to preventive healthcare utilization of HIV testing and breast examinations among female victims of IPV. Because women who are abused in relationships are vulnerable, their experience may influence their risk perception and may affect how they use healthcare compared to women who are not exposed to IPV.…”
Section: Discussionmentioning
confidence: 99%
“…One study has shown that women who were victims of sexual and/or physical violence were less likely to be up-to-date with their mammograms and Pap smear screenings. 44 It is likely that the Behavioral Model of Vulnerable Populations applies to preventive healthcare utilization of HIV testing and breast examinations among female victims of IPV. Because women who are abused in relationships are vulnerable, their experience may influence their risk perception and may affect how they use healthcare compared to women who are not exposed to IPV.…”
Section: Discussionmentioning
confidence: 99%
“…IPV may influence cancer survivorship through delays in diagnosis or cancer treatment, reducing QOL [3] during treatment or recovery, and ultimately affect survival. While IPV may [15–17] or may not [1819] be associated with receiving cancer screening at recommended intervals, IPV has been associated with not receiving follow-up care for pre-invasive disease [20] and with delays in receipt of care for invasive cancer [21]. IPV may impact women’s ability to obtain cancer treatment because those currently experiencing IPV are less likely to have health insurance, are more likely to live in poverty, and fewer transportation options [13, 22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, current literature inadequately describes preventive healthcare utilization among women exposed to IPV. Prior work examining IPV and prevention is limited by cross-sectional (Cronholm & Bowman, 2009; Lemon, Verhoek-Oftedahl, & Donnelly, 2002) or retrospective (Gandhi et al, 2010) study designs, examination of relatively few preventive services (Gandhi et al, 2010; Lemon et al, 2002; Loxton, Powers, Schofield, Hussain, & Hosking, 2009), or focus on women beyond reproductive age (Loxton et al, 2009) for whom IPV is less prevalent (McCauley et al, 1995). A few studies suggest that women exposed to IPV are less likely to receive clinical preventive services than the general population; for example, women with self-reported safety concerns in their relationships were less likely to report receiving cervical cancer screening within the past 12 months (Cronholm & Bowman, 2009).…”
Section: Introductionmentioning
confidence: 99%